Multiband Software Defined Radar for Soil Discontinuities Detection - S. Costanzo; F. Spadafora; O. H. Moreno; F. Scarcella; G. Di Massa (Journal of Electrical and Computer Engineering)
A multiband Software Defined Radar based on orthogonal frequency-division multiplexing technique is proposed in this work for an accurate soil discontinuities detection, taking into account also the dispersive behavior of media. A multilayer soil structure is assumed as a validation test to demonstrate the effectiveness of the proposed approach, by accurately retrieving the unknown thicknesses and permittivities of the soil layers.